A comparison of heart function and arrhythmia in clinically asymptomatic patients with beta thalassemia intermedia and beta thalassemia major. Issue 1 (2nd January 2017) - Amoozgar, Hamid; Zeighami, Samaneh; Haghpanah, Sezaneh; Karimi, Mehran
ABSTRACT: Background : The goal of this study was to compare heart function and arrhythmia in clinically asymptomatic patients with beta thalassemia intermedia and beta thalassemia major. Method : In this cross-sectional study, 60 patients with beta thalassemia major and 60 patients with beta thalassemia intermedia who had clinically no symptoms of arrhythmia and clinically normal heart function were evaluated using 24-hour ambulatory electrocardiogram monitoring and echocardiography. For data analysis SPSS ver.20 software was used. A P- value of less than 0.05 was considered statistically significant. Results : The mean age of the beta thalassemia intermedia patients was 24.18 ± 7.9 years and the mean age in beta thalassemia major was 24.38 ± 7.7 years ( P >0.05). Premature atrial contractions (PACs) were observed in 14 (23.3%) patients with beta thalassemia intermedia and in 22 (36.6%) beta thalassemia major patients. Premature ventricular contractions (PVCs) were detected in 8 (13.3%) patients in the beta thalassemia intermediate group and 16 (26.6) patients in the beta thalassemia major group, respectively. The left ventricular diastolic dimension, end-diastolic volume, and stroke volume were significantly higher in beta thalassemia intermedia group ( P <0.05). Pulmonary acceleration time as an indicator of pulmonary pressure was lower in beta thalassemia intermedia group. Conclusion : Both atrial and ventricular arrhythmias were more common in the beta thalassemia major group. Higher end-diastolic volume and stroke volume were detected in the beta thalassemia intermedia group. Pulmonary acceleration time was lower in the beta thalassemia intermedia group, which can be an indicator of higher pulmonary pressure.